Right inferior frontal gyrus and ventromedial prefrontal activation during response inhibition is implicated in the development of PTSD symptoms. Issue 1 (31st December 2022) - Powers, Abigail; Hinojosa, Cecilia A.; Stevens, Jennifer S.; Harvey, Brandon; Pas, Pascal; Rothbaum, Barbara O.; Ressler, Kerry J.; Jovanovic, Tanja; van Rooij, Sanne J.H.
ABSTRACT: Background: Inhibition is a critical executive control process and an established neurobiological phenotype of PTSD, yet to our knowledge, no prospective studies have examined this using a contextual cue task that enables measurement of behavioural response and neural activation patterns across proactive and reactive inhibition. Objective: The current longitudinal study utilised functional magnetic resonance imaging (fMRI) to examine whether deficits in proactive and reactive inhibition predicted PTSD symptoms six months after trauma. Method: Twenty-three (65% males) medical patients receiving emergency medical care from a level 1 trauma centre were enrolled in the study and invited for an MRI scan 1-2-months post-trauma. PTSD symptoms were measured using self-report at scan and 6-months post-trauma. A stop-signal anticipation task (SSAT) during an fMRI scan was used to test whether impaired behavioural proactive and reactive inhibition, and reduced activation in right inferior frontal gyrus (rIFG), ventromedial prefrontal cortex (vmPFC), and bilateral hippocampus, were related to PTSD symptoms. We predicted that lower activation levels of vmPFC and rIFG during reactive inhibition and lower activation of hippocampus and rIFG during proactive inhibition would relate to higher 6-month PTSD symptoms. Results: No significant associations were found between behavioural measures and 6-month PTSD. Separate linear regression analyses showed that reduced rIFG activation ( F1, 21 = 9.97, R 2 = .32, p = .005) and reduced vmPFC activation ( F1, 21 = 5.19, R 2 = .20, p = .03) significantly predicted greater 6-month PTSD symptoms; this result held for rIFG activation controlling for demographic variables and baseline PTSD symptoms (β = −.45, p = .04) and Bonferroni correction. Conclusion: Our findings suggest that impaired rIFG and, to a lesser extent, vmPFC activation during response inhibition may predict the development of PTSD symptoms following acute trauma exposure. Given the small sample size, future replication studies are needed. HIGHLIGHTS: Impaired inhibition may be an important risk factor for the development of PTSD following trauma, with less right inferior frontal gyrus and ventromedial prefrontal cortex activation during response inhibition predicting PTSD development.